Study of Spatial Domain and Frequency Domain Approach for Fingerprint Based Gender Classification - Anjikar, AV; Ramteke, K; Chauvan, S (International Journal of Computer Sciences and Engineering, 2020)
Each person’s fingerprint structure is unique and is developed for biometric authentication systems than others because fingerprints have advantages such as: feasible, differ from each other (distinct), permanent, accurate, reliable and acceptable all over the world for security and person identity. Fingerprints are considered legitimate proofs of evidence in courts of law all over the world. Fingerprint based gender classification can be studied using spatial domain and frequency domain approach. Spatial domain approach uses ridge related parameters like ridge count, ridge density, ridge width, ridge thickness to valley thickness ratio. Frequency domain approach do not work on physical parameters related to ridge, but work on measuring parameters like frequency and region parameters of an image. This paper compares one method of spatial domain approach and one method of frequency domain approach in terms of processing time, accuracy, simplicity in calculations and compatibility with other methods.